FACTORS RELATED TO INCREASING THE NUMBER OF CASES OF MEASURES AND THE ROLE OF NURSING - Cristina Dos Santos Batista , Antônia; Cristina Dos Santos Barbosa , Bárbara; Correia Nunes Eleutério, Eloá; Lima De Souza Silva, Vilma (Health and Society, 2021)
The aim of the present study was to analyze the factors related to the increase in the number of measles cases and the role of nursing in this context. This work was developed by a literature search with a descriptive approach, which will be based on a systematic literature review. Available in the Scientific Eletronic Library Online (SciELO), Virtual Health Library (VHL) and Latin American and Caribbean Literature in Health Sciences (Lilacs) databases. Published between 2010 and 2020, in English and Portuguese. With the following keywords, National Program for Immunization, Nursing, Measles and Anti-vaccine Movement. Measles is a viral, acute infectious disease, potentially serious, transmissible and extremely contagious. Being the only form of prevention through vaccines. Transmission occurs directly, through nasopharyngeal secretions excreted when coughing, talking, sneezing or breathing by infected people. Brazil received the certificate of elimination of the circulation of the measles virus by the WHO, declaring the region of the Americas free of measles. In 2019 new cases arose in Brazil. There are several factors related to this increase in the number of cases ranging from anti-vaccine movements, false news about vaccination and poor vaccination coverage. Therefore, the objective is to relate these factors, highlighting the performance of nursing, showing some control strategies and seeking a solution to the problem.